Pengembangan Utility Pembuatan Grafik Data Penyelesaian Skripsi Pada Sistem Surat Jurusan Ilmu Komputer Fmipa Universitas Lampung - Dwi Sakethi; Didik Kurniawan; Laurentika Lanova Pandiangan (Jurnal Komputasi, 2014)
This research was conducted on the development of information systems supporting the completion of a thesis in the form of graphics on the letter System. Development is done by adding the Menu Duration of Study, Old Settlement thesis, recapitulation data as well as data guidance thesis. The development aims to improve the performance of the Secretary of the Department in managing student thesis data. In this development using the PHP programming language function library Kendo and MySQL as the database. This application has been applied to the Information Systems Department of Computer Science, University of Lampung.Â Key Word: Letter System, Graphics Menu, kendo.